PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP NEGERI 4 ALASA PADA KURIKULUM MERDEKA - Zalukhu, Putri Wulandari; Mendrofa, Ratna Natalia; Telaumbanua, Yakin Niat; Lase, Sadiana (STKIP PGRI Situbondo, 2025)
This study was motivated by the low mathematics learning outcomes among students, their limited engagement during the learning process, and the unappealing presentation of learning materials at SMP Negeri 4 Alasa. The purpose of this research was to examine the effect of the Project-Based Learning (PjBL) model on students' mathematics learning outcomes within the Merdeka Curriculum. This experimental study employed a quasi-experimental method using a Nonequivalent Control Group Design. The research subjects included all seventh-grade students at SMP Negeri 4 Alasa, with class VII-B (30 students) serving as the experimental group taught using the PjBL model, while class VII-A (30 students) served as the control group using conventional teaching methods. The instrument used was an essay-based learning outcome test comprising five questions. Data analysis results showed that the calculated t-value was greater than the critical t-value (4.855 > 1.671). Thus, H0 was rejected, and Hₐ was accepted, indicating that the implementation of the Project-Based Learning (PjBL) model had a significant effect on students' mathematics learning outcomes under the Merdeka Curriculum.